1997
DOI: 10.1152/jappl.1997.83.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of sustained isocapnic hypoxia on ventilation in men and women

Abstract: Sleep-related respiratory disturbances are more common in men than in premenopausal women. This might, in part, be due to different susceptibilities to the respiratory depressant effects of hypoxia. Therefore, we compared ventilation during 10 min of baseline room-air breathing and 20-min sustained isocapnic hypoxia (fractional inspired O2 = 11%, arterial saturation of O2 approximately 80%) followed by 10 min of breathing 100% O2 in 10 normal men and in 10 women in the follicular phase of the menstrual cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
4
13
0
Order By: Relevance
“…Other studies found an HVR that was greater in men compared to women, with a range of 39–110% [15,16,17]. There also are data showing no gender difference [18,19, 20]. Prior studies evaluated between 11 to 67 subjects in total, in comparison to the 427 participants with reliable data in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies found an HVR that was greater in men compared to women, with a range of 39–110% [15,16,17]. There also are data showing no gender difference [18,19, 20]. Prior studies evaluated between 11 to 67 subjects in total, in comparison to the 427 participants with reliable data in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Wenninger studied the effects of age and sex on HVR in rats and reported a greater HVR in females than in males 20 months old (Wenninger et al 2009). Regardless of age, a majority of authors found no difference in HVR between the sexes (Sajkov et al 1997; Teppema & Dahan, 2010). In women, an enhancement of HVR was described during the luteal phase compared with the follicular phase (Schoene et al 1981; White et al 1983) and during pregnancy (Moore et al 1987; Hannhart et al 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Wenninger studied the effects of age and gender on HVR in rats and reported a greater HVR in females than in males at old age (Wenninger et al, 2009). Regardless of age, a majority of authors found no difference in HVR between genders (Sajkov et al, 1997;Teppema and Dahan, 2010). In women, an enhancement of HVR was described during the luteal phase compared to the follicular phase (Schoene et al, 1981;White et al, 1983) and during pregnancy (Moore et al, 1987;Hannhart et al, 1989).…”
Section: Menopause and Ventilatory Responsementioning
confidence: 99%